A novel approach for safe and automated implementation of far ultraviolet-C light decontamination in clinical areas - Samir Memic; Jennifer L. Cadnum; Andrew Osborne; William A. Rutala; Curtis J. Donskey (Cambridge University Press, 2024)
A novel wall-mounted far ultraviolet-C (UV-C) light technology providing automated delivery of far UV-C only when people are not present reduced methicillin-resistant Staphylococcus aureus in a patient room and equipment room. The safety feature that discontinues far UV-C output when people are detected was effective in preventing far UV-C exposure.